Catheter Ablation of Cardiac Arrhythmias A Practical Approach - Schmitt, C.; Deisenhofer, I.; Zrenner, B.; SpringerLink (Online service) (Heidelberg : Steinkopff : Imprint: Steinkopff, 2006)
Catheter ablation of cardiac arrhythmias is an important field of interventional cardiology. This comprehensive overview is a practical guide for - exact diagnosis of cardiac arrhythmias - mapping of cardiac arrhythmias with newest 3D technology - catheter ablation of various arrhythmias from WPW syndrome to atrial fibrillation. Colored intracardiac tracings as well as fluoroscopic and 3D mapping images reflect the situation in the EP lab and lead you step by step to the right diagnosis and successful ablation.
Basic principles -- Ablation of cardiac arrhythmias — energy sources and mechanisms of lesion formation -- Three-dimensional electroanatomic mapping systems -- Accessory pathways -- Atrioventricular nodal reentrant tachycardia -- Cavotricuspid isthmus-dependent atrial flutter — common-type atrial flutter -- Atypical atrial flutter -- Focal atrial tachycardia -- Ventricular tachycardia -- Catheter ablation of atrial fibrillation -- Mapping and ablation in the pediatric population -- Mapping and ablation in congenital heart disease.
Keywords: Cardiology; Internal medicine; Cardiology; Internal Medicine